AB1078 Impact of pre-screening on rheumatology outpatient clinic practice. (15th June 2017) - Orr, C; McElvaney, O; McQuillan, M; Hussein, M; Donnelly, S; McCarthy, G; McCarthy, C
Abstract : Background: Chronic rheumatological diseases are predominantly managed in an outpatient setting, and these out patient clinics constitute a significant workload for rheumatolgy clinicicians. When unnecessary outpatient visits occur, service provision to those most in need of rheumatology review, both new referrals and those with established diagnoses in need of urgent review, is compromised. There is an evidence base for such screening in secondary care centres from other internal medicine disciplines (1). Objectives: To determine the impact of introducing pre-clinic screening, and exploring the potential for follow up using telephone, by a physician extender (PE), on attendances at a rheumatology outpatient department. Methods: A retrospective chart review of all patients attending a rheumatology outpatient clinic was performed over a 4-week period, 15/08/2016- 09/09/2016. Patients were categorized into new or follow-up attendees and the follow-up patients were further subcategorized into 1 of 4 groups: A) Attending to receive results of investigations requiring no further treatment; B) Attending with a chronic rheumatological disease requiring no active change in management; C) Attending to receive results of investigations requiring further treatment; D) Attending with a chronic rheumatological disease requiring active change in management. Patients in categories A and B, may be safely managed by a phone call from a physician, or PE. Those in C and D would need to be reviewed in clinic, following triage by phone using a PE. Results: 232 subjects were included (5 category A, 118 category B, 4 category C, 105 category D). 123 (53.0%) could be managed by phone utilizing a PE, thus obviating the need for review in clinic. The remaining patients could be triaged by telephone by a PE, and the schedule for review adjusted to prioritise those most in need of review. It is likely that such a strategy for reviewing patients would be more clinically efficient, have a greater impact on patient well-being, and be cost-saving. Conclusions: Routine pre-screening for patients attending rheumatology clinics should be considered to improve effectiveness of the commodity rheumatology expertise. References: Donnellan, F., Harewood, G.C., Cagney, D., Basri, F., Patchett, S.E. and Murray, F.E., 2010. Economic impact of prescreening on gastroenterology outpatient clinic practice. Journal of clinical gastroenterology, 44(4), pp.e76-e79. Disclosure of Interest: None declared